2019
DOI: 10.5296/jas.v7i2.14758
|View full text |Cite
|
Sign up to set email alerts
|

Perceived Effects of Climate Variability on Cassava Production among Small Scale Farmers in Anambra State, Nigeria

Abstract: Climate variability is one of the predominant themes in agricultural research. Climate variations can seriously affect agricultural production. It brings about changes in weather patterns which in turn give rise to imbalances in seasonal cycles, harm to ecosystems and water supply affecting agriculture and food production. Extreme weather events such as floods, landslides and drought are caused by climate variation. Studies have shown that root crops such as cassava are most vulnerable to the impact of climate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 2 publications
0
3
0
Order By: Relevance
“…The implication of these findings was that there were ample hands to produce more ground and will worked enthusiastically. This study concurs with the findings of (Anarah et al 2017) Household size determines the number household that can provide labour in the farm. The results in the Table 2 indicated that majority of (41%) had 9 to 11, followed by (36%) had 5 to 8 members.…”
Section: Socio-economic Characteristic Of the Respondentssupporting
confidence: 92%
“…The implication of these findings was that there were ample hands to produce more ground and will worked enthusiastically. This study concurs with the findings of (Anarah et al 2017) Household size determines the number household that can provide labour in the farm. The results in the Table 2 indicated that majority of (41%) had 9 to 11, followed by (36%) had 5 to 8 members.…”
Section: Socio-economic Characteristic Of the Respondentssupporting
confidence: 92%
“…Consequently, 47.9% of the cassava producers reported greater land access. This adaption strategy was due to land fragmentation problems that prevent large-scale cassava farming (Anarah et al, 2019). Erosion control measures were adopted by 96.4% of the cassava farmers, this implies that the cassava farmers took to erosion control measures to prevent the erosion of the vegetative soil surface, newly planted cassava stems, mulch materials and manure applications.…”
Section: Cassava Farmers' Adaptation Strategiesmentioning
confidence: 99%
“…Rainfall increases spawn a variety of pests and diseases that heavily consume cassava leaves, lowering the photosynthetic activity of cassava plants (Paul et al, 2019). It is reported that Nigeria's cassava crop would continue to decrease as long as climate change persists (Anarah et al, 2019). Nigeria is the sixth least prepared to adapt to climate change and the 53rd most vulnerable nation, according to the 2021 Notre Dame Global Adaptation Index (ND-Gain Country Index, 2021).…”
Section: Introductionmentioning
confidence: 99%
“…Crop farmers suffer the effects of climate change due to obstacles such as their reliance on rain-fed agriculture, their limited financial resources, their inability to adapt, their inadequate infrastructure, their illiteracy, and their inability to diversify (Anarah et al, 2021, Pipitpukdee et al, 2020. One of the pronounced challenges is the lack of access to crucial information on climate change, which consequently affects their level of awareness and potential for resilience and adaptation.…”
Section: Introductionmentioning
confidence: 99%